The Strategic Issues Of Economic Development Of Border Area Of Indonesia - Malaysia - Abas Sunarya; Sudaryono Sudaryono (UNIVERSITAS RAHARJA, 2016)
On the land, Indonesia is bordered by three countries: Malaysia, Papua New Guinea and Timor Leste.Whereas, in Indonesia sea area bordered by 10 countries: India, Malaysia, Singapore, Thailand,Vietnam, Philippines, the Republic of Palau, Australia, East Timor and Papua New Guinea. Most ofthe border region in Indonesia is still an underdeveloped area with less facilities and infrastructure ofsocial and economic. Formulation of the problem are: 1. How do the condition of the socio-economicand culture in the border of Indonesia - Malaysia? 2. What is the condition of infrastructure in theborder and what is the urgent infrastructure to be built? 3. What are policy and strategy of theIndonesian government of the border of society development between Indonesia (Entikong) andMalaysia (Sarawak)? The purpose of writing are: 1. Comparing the condition of the socio-economicand culture of border both Indonesia and Malaysia. 2. Comparing the condition of the infrastructureof border both Indonesia and Malaysia and determining the infrastructure to be built. 3. Describingthe Indonesian government policy and strategy in development acceleration of economic society in theborder between Indonesia, especially Entikong Sub-District of Sanggau Regency West Kalimantanand Malaysia (Sarawak). Although, the commitment and the governments policy have given a higherpriority in the reorientated development of border, which those of security (security approach) into awelfare orientation (prosperity approach), but overall, the issue of society development in Indonesiaborder, especially the District Entikong Sanggau Regency West Kalimantan and Malaysia (Sarawak)so far can be said that are still not getting proportional attention. The indication, though a variety ofpolicies, regulations or laws relating to efforts to accelerate economic development of border societieshave been made. Various issues and problems are faced by the border, both land and sea borders canbe solved by more focused and targeted on six aspects, these are policy, economic and socio-cultural,defense and security, natural resources management, institutional and management authority, as wellas cooperation inter nations.